Settlements analysis of PVD installation in soft soil using plaxis 3D - Allawi, Ahmed Mohammed Hasan (2020)
Recent years, several of construction projects are built on soft soil. In accordance with the proprieties of soft soil, the construction on soft soil always leads to settlements. Vertical drain such as prefabricate vertical drain (PVD) has been successfully applied in many projects as soft soil ground improvement method. However, some of the solutions that existed to accelerate the consolidation process are not applicable for the multi-layered soft soil and optimum spacing and length of PVD has not been established due to limitation of 2D analysis. In this study, finite element analysis is applied to verify the efficiency of modelling of vertical drain in subsoil using computer software, PLAXIS 3D. This study will also analyses the effect of prefabricate vertical drain (PVD) at optimum horizontal spacing and length of (PVD) via different soil models those are Mohr Coulomb Model and Hardening Soil Model.